1)$\left\{\begin{matrix} 3\sqrt{(2x^{2}+y)(x^{2}+2y^{2})=4y^{2}-y+4} & & \\ 4x^{2}+4y^{2}+y=22& & \end{matrix}\right.$
2)$\left\{\begin{matrix} x^{2}+xy+\frac{2x}{y}=4 & & \\ \frac{18}{(x+y)^{2}}=y(y-x)& & \end{matrix}\right.$
3)$\left\{\begin{matrix} \frac{1}{x}+\frac{1}{y}=0 & & \\ (\frac{1}{\sqrt[3]{x}}+\frac{1}{\sqrt[3]{y}})(1+\frac{1}{\sqrt[3]{x}})(1+\frac{1}{\sqrt[3]{y}})& & =18 \end{matrix}\right.$
4)$\left\{\begin{matrix} \sqrt{\frac{x^{2}+y^{2}+xy}{3}}+\sqrt{\frac{x^{2}+ y^{2}}{2}=x+y}& & \\ x\sqrt{2xy+5x+3}=4xy-5x-3& & \end{matrix}\right.$